Ayurvedic Management of Pittaja Kustha (Erythrodermic Psoriasis) Based on the Colour of Lesions (AYUSHDHARA, 2025)
Kustha, an umbrella term in Ayurveda for various skin disorders, is characterized by lesions of differing colours. Classification of Kustha and its management based on Dosha predominance and type of lesions is mentioned in various Ayurveda texts. However, we also find a simple way of formulating management of Kustha based on colour of lesions. This case study investigates the Ayurvedic management of Pittaja Kustha, focusing on the colour of lesions as a basis for treatment. Objectives: To assess the effectiveness of Ayurvedic treatments tailored to the colour of Kustha lesions with respect to Pittaja kustha and their impact on patient outcome. Methods: A case study was conducted on a patient with red coloured Kustha lesions. Treatments were customized based on colour; Virechana (purgation therapy) and Jaloka (leech therapy) were administered to the patient. Results: The patient showed significant improvement in red types of lesions. Red lesions improved with Virechana and Jaloka (leech therapy). Overall, the patient's skin condition and general health enhanced markedly. Conclusions: This study highlights the efficacy of colour-based Ayurvedic management of Pittajakustha, demonstrating that individualized treatment protocols can significantly improve patient outcomes.